2020
DOI: 10.1080/2331205x.2020.1794500
|View full text |Cite
|
Sign up to set email alerts
|

Energy expenditure estimation of a moderate-intensity strength training session

Abstract: An accurate method for quantifying associated metabolic cost has yet to be developed for a strength training session (ST). The aim of this study was to quantify the energy expenditure (EE) in an ST session composed of eight exercises at moderate intensity using indirect calorimetry and, from the values obtained, develop a prediction equation for estimating EE. Fifteen males (22.9 ± 2.61 years old), with at least 12 months of experience in ST performed one session of strength training composed of 8 exercises. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Most of the available literature found regression models to predict EE using body composition (p < 0.001), ambient temperature (p = 0.004) [10], and exercise intensity-loads and volume (R 2 = 0.61 and p < 0.05) [9] etc. A study by Farinatti and Neto reported that total energy expenditure (EE) is mainly affected by muscle mass (p > 0.001) during five sets of ten repetitions with 15 RM loads of moderate-intensity horizontal leg press and chest fly with 1 and 3 min rest intervals [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the available literature found regression models to predict EE using body composition (p < 0.001), ambient temperature (p = 0.004) [10], and exercise intensity-loads and volume (R 2 = 0.61 and p < 0.05) [9] etc. A study by Farinatti and Neto reported that total energy expenditure (EE) is mainly affected by muscle mass (p > 0.001) during five sets of ten repetitions with 15 RM loads of moderate-intensity horizontal leg press and chest fly with 1 and 3 min rest intervals [21].…”
Section: Discussionmentioning
confidence: 99%
“…of sets x no. of repetitions) and X 2 = session time (minutes) [9]. Another study predicted resting energy expenditure (REE) equations in master athletes using body weight, gender, age, height, fat-free mass (FFM), fat mass (FM), temperature, training hours, phase angle, and kind of sports (R 2 = 0.55-0.69).…”
Section: Introductionmentioning
confidence: 99%